2016
DOI: 10.1128/jvi.02670-15
|View full text |Cite
|
Sign up to set email alerts
|

A Single Amino Acid Change in the Marburg Virus Matrix Protein VP40 Provides a Replicative Advantage in a Species-Specific Manner

Abstract: Marburg virus (MARV) induces severe hemorrhagic fever in humans and nonhuman primates but only transient nonlethal disease in rodents. However, sequential passages of MARV in rodents boosts infection leading to lethal disease. Guinea pig-adapted MARV contains one mutation in the viral matrix protein VP40 at position 184 (VP40 D184N ). The contribution of the D184N mutation to the efficacy of replication in a new host is unknown. In the present study, we demonstrated that recombinant MARV containing the D184N m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
(61 reference statements)
0
16
0
Order By: Relevance
“…The generation of recombinant viruses from cDNA plasmids has been developed for several filoviruses as full-length genome or life imaging systems [287][288][289][290] . The full-length genome systems expressing reporter genes reduce the time and effort needed to detect virus growth but still require biosafety level 4 (BSL-4) biocontainment and have the potential to be attenuated.…”
Section: Box 4 | Screening Systems For Drug Developmentmentioning
confidence: 99%
“…The generation of recombinant viruses from cDNA plasmids has been developed for several filoviruses as full-length genome or life imaging systems [287][288][289][290] . The full-length genome systems expressing reporter genes reduce the time and effort needed to detect virus growth but still require biosafety level 4 (BSL-4) biocontainment and have the potential to be attenuated.…”
Section: Box 4 | Screening Systems For Drug Developmentmentioning
confidence: 99%
“…This mutation, which occurs in the flexible linker region between the VP40 N- and C-terminal domains [90], has no effect on the ability of VP40 to inhibit the IFN response in guinea pig or human cells. Instead, D184N contributes to VP40’s role as the viral matrix protein [116]. In guinea pig but not human cells, the D184N mutation improves the ability of VP40 to attract nucleocapsids to the site of virion budding, and it improves budding, itself.…”
Section: Rodent-adapted Filoviruses and Their Mutationsmentioning
confidence: 99%
“…The mutation also reduces the suppressive effect that VP40 has on viral RNA synthesis in guinea pig cells, thereby improving replication and transcription. Accordingly, recombinant MARV containing only the D184N mutation in VP40 outgrows WT-MARV in guinea pig cells, although whether the mutation is solely responsible for the increase in GPA-MARV/Mus virulence remains to be determined [116]. Two other guinea pig-adapted marburgviruses have been generated, GPA-MARV variant Angola (GPA-MARV/Ang) and GPA-RAVV; however, neither of these viruses possesses the D184N mutation (Fig.…”
Section: Rodent-adapted Filoviruses and Their Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study showed that the D184N mutation in VP40 negated its suppressive function on MARV polymerase activity specifically in guinea pig cells, and thus conveys a species-specific improved viral fitness (Koehler et al, 2015). We therefore presumed a functional co-selection of the mutations in VP40 and in L, and tested the function of L mutants in the presence of VP40 and VP40 D184N .…”
mentioning
confidence: 99%